Training on the Use of AI Tools to Support High School/Vocational High School Education in Jakarta - S.Pd., MT, Herianto; Setiyaningsih, Timor; Nur Afifah, Linda (JEPTIRA, 2024)
The numerous facets of education have been significantly transformed by artificial intelligence (AI) technology. It is currently in widespread use to improve the efficiency of learning, provide personalized learning experiences, and assist instructors in managing administrative responsibilities. In addition to its advantages, the integration of AI into education also poses obstacles, including ethical concerns, excessive dependence on technology, and doubts about the validity of learning outcomes. The objective of this community service activity is to investigate the potential benefits and drawbacks of AI applications in education, as well as to offer suggestions for their effective implementation. Educators can employ AI more responsibly and effectively by comprehending both the advantages and obstacles. The training is administered online to ensure that a diverse audience, including high school and vocational school teachers in Jakarta, has access to the material. It commences with a pre-test to assess the initial comprehension of AI tools among participants. A post-test is administered at the conclusion of the session to assess the extent to which the knowledge has been enhanced as a result of the training